EFFECT OF FLOW WATER VELOCITY ON HEMATOLOGY COMPONENT IN IMPROVING QUALITY OF TIGER GROUPER JUVENILE (Epinephelus fuscoguttatus) - Marcelien Dj. Ratoe Oedjoe; E. Suprayitno; Aulanni' am; E.Y. Herawati (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The flow water velocity is closely correlated to oxygen demand. Oxygen plays an important role as the indicator of fish blood. The objective of research is to acknowledge red blood cell, hematocrit, hemoglobin, and white blood cell of grouper larvae given with flow water velocity treatments. Research begans from June 2011 to September 2011 at Lampung Marine Aquaculture Center. Juvenile with 7-9 cm length and 15-17 g/fish weight were tested using complete random design with three treatments of flow water velocity, i.e. 1.25 m/sec (A), 1.00 m/sec (B), and 0.75 m/sec and control treatment. All treatments had 3 replications. Result of research indicates that flow water velocity had obvious effect on red blood cell, hematocrit, hemoglobin, and white blood cell. Red blood cell total was the highest in treatment of 1.25 m/second, counted for 2,922,666 cells/ml. It was followed by treatment B with 2,816,000 cell/ml, treatment C with 2,763,000 cell/ml and control with 2,573,333 cell/ml. The highest hemoglobin was found in treatment A, followed by B, C, and control treatments. The highest hematocrit rate was seen in treatment A, followed by B, C and control treatments. The highest white blood cell total was discovered in control, followed by C, B and A treatments.